Experimental Study on Mechanical Properties and Cracking Behaviors of T-Shaped Flaw-Contained Rock-like Materials Under Cyclic Loading - Cui, Lan; Liu, Yi; Sheng, Qian; Xiao, Ping (Frontiers in Earth Science, 2021)
The geotechnical hazards such as debris flows, rock falls in slopes, rock collapse and rockburst in the underground mining or caverns are tightly correlated to the mechanical behaviour of the natural rock mass stability. Strength and failure mode of the natural rock mass are governed by the presented fissures. In this paper, samples containing T-shaped fissures with different geometry were prepared by rock-like materials and tested under varying uniaxial cyclic loading compression. The effect of T-shaped fissures with different geometry, the strain rate and loading frequency on the strength of tested samples are studied, and the failure mode of the samples containing T-shaped cross fissures under different working conditions were observed. The results show that the function of the minor fissures is not negative totally, and the strength of T-shaped fissure samples containing major fissure with different inclination angles presents varying trend with the increasing included angle between the major and minor fissures. Moreover, the strength of the cracked samples increases with the increase of the strain rate and loading frequency, and the larger the included angles between the major and minor fissures, the T-shaped fissure sample is more sensitive to the change of frequency, but without noticeable linear correlation relationship between the strength of the sample and the included angles between the major and minor fissures. In addition, the existence of the minor fissures has a significant impact on the failure mode of the sample, and the failure mode of the samples containing T-shaped cross fissures of the same geometry under the uniaxial compression and the uniaxial cyclic load is equivalent.